Effectiveness of Giving Loss of Rosella Tea on Decreasing Blood Pressure in Elderly Patients of Hypertension in Working Areas Puskesmas Sengkol Village Sengkol 2 District Pujut Regency of Central Lombok - Pratama, Edy Surya; Pratiwi, Dita Retno; Jupriadi, Lalu (Jurnal Kesehatan Qamarul Huda, 2019)
Hypertension is a circulatory system disorder that causes a rise in blood pressure above the normal value, which exceeds 140/80 mmHg. The data explained from the number of elderly visits Hypertension sufferers at the Sengkol Health Center each year experienced an increase. And from the results of interviews, the highest incidence of hypertension is compared to the health Central Lombok District. So the author is interested in doing research. This study aims to determine the effectiveness of the administration of rosella tea to reduce blood pressure in elderly people with hypertension. This type of research is pre-experiment. The population in this study were 45 people with a total sample of 14 respondents, this study used bivariate analysis using paired t-test. The average elderly blood pressure before being given rosella tea is 152.86 / 93.57 mmHg, while after being given rosella tea to 147.14 / 87.86 mmHg. In this study there was a significant effect on the decrease in cystole blood pressure with p-value 0,000 < (0,05), and for diastolic blood pressure with p-value 0,000 < (0,05). Suggestions in this study as input for health central in improving services and care for patients who have hypertension.